CELL VIABILITY, PHYSICOCHEMICAL AND SENSORY CHARACTERISTICS OF PROBIOTIC COCONUT JUICE DURING COLD STORAGE - Olaide, Olawunmi Ajibola; Samuel, Lihan; Ahmad, Husaini; Cirilo Nolasco, Nolasco-Hipólito; Octavio, Carvajal-Zarrabal; Shahrul Razid, Sarbini; Sharifah Aminah, Syed Mohamad (Penerbit UMT, 2021)
Probiotic fermentation has gained considerable attention in the pharmaceutical and food industries. Milk-based products are not in demand among vegetarians, people with allergies to certain proteins, and lactose-intolerant consumers. Therefore, there is a genuine interest in the production of crop juice-based probiotic beverages with probiotic potentials. The objective of this study is focused on the development and storage of probiotic coconut juice using lactic acid bacteria (LAB) as a starter. The viability of the probiotic, its physicochemical properties, and antibacterial potentials of the stored probiotic coconut juice employing LAB (Lactobacillus casei ATCC 393, Lactobacillus plantarum ATCC20174, Lactobacillus rhamnosus ATCC 7469, and Lactococcus lactis IO-1) as a single starter culture were studied. Sensory tests were also performed on the samples. There was an increase in total acidity production and a decrease in pH and brix levels, as well as phenolic, antioxidant and tannin contents during the refrigerated condition. At weeks three and four, coconut juice inoculated with L. lactis IO-1 samples had the highest total acidity (1.32%). However, the level of phenolic compound, antioxidant, and tannin contents showed a slight decrease during storage. The probiotic strains were viable throughout the refrigerated condition. L. lactis IO-1 showed greater viability compared with other strains (8.426 log CFU/mL). There were no significant differences between all the samples in terms of taste, aroma, colour and appearance. It could be inferred from this study that high acidity and the presence of inhibitor phenolic compounds in the probiotic coconut juice have no negative impact on the viability of the probiotics and antibacterial potential of the samples throughout storage. Hence, probiotic fermentation could provide an alternative outlet for coconut juice utilization, and could be used to produce novel probiotic beverages for consumers, especially in terms of sports nutrition.